O processo de desenvolvimento de sistemas de gestão em organizações hospitalares e a importância da profissionalização de seus dirigentes: considerações a partir de um processo de consultoria no Hospital Evandro Chagas - Barbosa, Pedro Ribeiro (1996)
This dissertation discusses the process of transformation of the management system in the Evandro Chagas Hospital/Fiocruz. It focuses on the characteristics of public hospital organization and the challenge of coordinating the medicai and research work. It presents and discusses the principies of the mamagement system, from an understanding of strategic and situational planning of Carlos Matus's theories of macro-organizations. Finally, it considers that the process of management development of the hospital organizations, starting from the experiences in focus, should be understood in at least two mutually conditional dimensions: firstly, at the levei of perfection of the management strutures and metlhods; secondly, at the levei of professionalization of the hospital managers.